Arahan Revitalisasi Bangunan Cagar Budaya dan Bangunan Diduga Cagar Budaya di Kota Tua Senapelan Kota Pekanbaru - Muhammad Shadam Syafsafa Adsya; Ira Safitri Darwin (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. The Senapelan City is an ancient city and the founding nucleus of Pekanbaru, a city that has existed since precolonial times. Its role has transformed over time. In the past, Senapelan served as a strategic trading route and a loading and unloading point for goods conducted by the VOC (Dutch East India Company). During the colonial period, the Dutch established several trading offices towards the south. After Independence, the development of Pekanbaru shifted towards the south, leading to the abandonment of the Senapelan area. Consequently, many historical buildings deteriorated, were left abandoned, and eventually succumbed to the ravages of time. This research is intriguing to be conducted due to the presence of 13 Cultural Heritage Buildings (BCB) managed by the Regional Government and 18 Buildings with Cultural Heritage Potentials (BDCB) with varying conditions, ranging from well-maintained to neglected and even ruined structures. The study aligns with the zoning of the BCB that has been previously conducted in the Old Town of Senapelan. Based on this background, the research aims to formulate guidelines for the revitalization concept of the Old Town of Senapelan. The research adopts a qualitative approach using the hermeneutic method. The research findings indicate that the guidelines for the revitalization of the Old Town of Senapelan should consider the condition of the cultural heritage buildings and their historical value. This can be achieved through reconstruction, consolidation, rehabilitation, restoration, and maintenance approaches.. Abstrak. Kota Senapelan adalah kota tua cikal bakal berdirinya kota Pekanbaru yang sudah ada sejak dari zaman prakolonial. Peran kota ini bertransformasi dari waktu ke waktu. Pada masa lampau Senapelan merupakan jalur perdagangan strategis dan menjadi tempat bongkar muat barang yang dilakukan oleh VOC. Pada masa kolonial, Belanda membangun beberapa kantor dagang ke arah selatan. Pasca Kemerdekaan pembangunan Kota Pekanbaru mengarah ke arah selatan. Sejak saat itu Kawasan Senapelan mulai ditinggalkan, sehingga banyak bangunan bersejarah yang rusak, terbengkalai, hingga hancur dimakan umur. Penelitian ini menarik untuk dilakukan karena terdapat 13 BCB yang di kelola oleh Pemerindah Daerah dan terdapat 18 BDCB dengan kondisinya yang berbeda-beda mulai dari bangunan yang terawat hingga terbengkalai bahkan hancur. Penelitian ini sesuai dengan zonasi BCB yang sudah dilakukan pada kawasan Kota Tua Senapelan. Merujuk latar belakang tersebut penelitian ini dilakukan dengan tujuan menyusun arahan konsep revitalisasi Kawasan Kota Tua Senapelan. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode hermeneutik. Hasil penelitian menunjukan arahan revitalisasi Kawasan Kota Tua Senapelan merujuk pada kondisi bangunan cagar budaya dan nilai sejarah, yaitu dengan rekonstruksi, konsolidasi, rehabilitasi, restorasi dan Pemeliharaan.